THE STRATEGY COMMUNICATION OF MAJELIS ULAMA INDONESIA KOTA MEDAN IN SOSIALIZATION OF HALAL CERTIFICATION - Erni Suyani; Sri Mulyani; Maria Ulfa Batubara (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
The results of this study indicate that the MUI communication model in Medan in promoting halal certification emphasizes mass communication. The selected communication media include: Print media, such as: newspapers (newspapers), magazines, article writing, brochures. Electronic media, such as: TV and radio. Special events, such as: MTQ, Counselling and Bazaar, by opening a stand containing halal products. There are also obstacles and challenges in socializing halal certification. The inhibition is in the form of low participation of business actors (producers) of food, drugs, and cosmetics that register their products. Then, from the community itself it is still not careful enough to select halal products for consumption. While the challenge is still to find halal labels that do not originate from MUI, and forgery of halal labels.